2021
DOI: 10.1002/advs.202101166
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐Directed Patterning for Versatile Validation and Characterization of a Lipid‐Based Nanoparticle Model of SARS‐CoV‐2

Abstract: Lipid‐based nanoparticles have been applied extensively in drug delivery and vaccine strategies and are finding diverse applications in the coronavirus disease 2019 (COVID‐19) pandemic—from vaccine‐component encapsulation to modeling the virus, itself. High‐throughput, highly flexible methods for characterization are of great benefit to the development of liposomes featuring surface proteins. DNA‐directed patterning is one such method that offers versatility in immobilizing and segregating lipid‐based nanopart… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…In contrast to aCD63 beads, for which we observed no significant correlation ( r 2 = 0.81, p = 0.09), the fluorescence intensity of ACE2 beads was strongly correlated with a spike liposome number ( r 2 > 0.99, p = 0.0024). These data strongly support that cholesterol-oligonucleotides self-embed in the membrane of lipid bilayer nanoparticles, consistent with previous reports of cholesterol-based exosome and liposome labeling, , and that ACE2 beads can readily sequester lipid bilayer nanoparticles displaying spike protein for subsequent qPCR-based detection. The bead-based isolation of the nanoparticles is crucial to DIVER’s robustness to sample dilution.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…In contrast to aCD63 beads, for which we observed no significant correlation ( r 2 = 0.81, p = 0.09), the fluorescence intensity of ACE2 beads was strongly correlated with a spike liposome number ( r 2 > 0.99, p = 0.0024). These data strongly support that cholesterol-oligonucleotides self-embed in the membrane of lipid bilayer nanoparticles, consistent with previous reports of cholesterol-based exosome and liposome labeling, , and that ACE2 beads can readily sequester lipid bilayer nanoparticles displaying spike protein for subsequent qPCR-based detection. The bead-based isolation of the nanoparticles is crucial to DIVER’s robustness to sample dilution.…”
Section: Resultssupporting
confidence: 91%
“…As SARS-CoV-2 is an enveloped virus, we first employed a liposome model to verify the labeling of lipid-bilayer nanoparticles with synthetic oligonucleotides and their specific capture onto beads via the spike–ACE2 interaction. ACE2 is the primary receptor on human cells to which SARS-CoV-2 binds with high affinity and has been used in several other SARS-CoV-2 technologies for virus trapping and detection. The liposome model we used displayed the S1 subunit of the SARS-CoV-2 spike protein, which contains the receptor binding domain (RBD), in an orientation that binds to ACE2 (ref , hereafter referred to as spike liposomes). Spike liposomes were comparable in diameter (125.9 ± 27.3 nm; Figure S2a) to SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, earlier studies have demonstrated how viruses, or parts thereof, can be assembled bottom-up and this ambitious approach has been recently transferred into the realm of SARS-CoV-2 research 21 , 22 . Intriguingly, in vitro reconstitution of the SARS-CoV-2 viral envelope and integration of the spike glycoprotein on lipid vehicles revealed how inflammatory fatty acids are exploited to trigger a molecular switch that couples local inflammation states to SARS-CoV-2 infectivity 23 25 .…”
Section: Bottom-up Engineering Of Life-like Systemsmentioning
confidence: 99%